Kajian Kualitas dan Tingkat Pelayanan Jalur Pedestrian di Koridor Jalan Khatib Sulaiman Kota Padang - Humaira Miftahur Rahmi; Parfi Khadiyanta (Teknik PWK (Perencanaan Wilayah Kota), 2018)
Condition of pedestrian way at Jalan Khatib Sulaiman is generally not good and many problems, that is suffered a lot of damage, the occurrence of the transfer function, and narrowing space pedestrian path. Based on the formulation of the problem then the question of this research is How is the Quality and Level of Service of Pedestrian in Khatib Sulaiman Street Corridor Padang City? The purpose of this research is to know the quality and pedestrian level of service on Khatib Sulaiman Street corridor. Pedestrian ways quality analysis was conducted using PEQI approach, while level of service analysis used Level Of Service (LOS) analysis with High Capacity Manual (HCM 2000) method. The method used in this research is quantitative method with descriptive analysis and evaluative analysis. Based on the analysis known that the personal characteristics of pedestrians are 18-50 years old with the type of student. The activity that dominates on the pedestrian track is important activity. Types of land use around the pedestrian lanes are residential areas, trade & services, offices, schools/campuses, and the mosque of Kota Padang as a tourist attraction and landmark. Based on the land use, the pattern of pedestrian movement is dominantly moving from the settlement area to the commercial area. The results of pedestrian path quality analysis showed the quality of the intersections are in category III (basic category) and the quality of the path in category IV (bad category). The result of level of service analysis shows that is service level based on current or based on entrance space at service level D (bad service level). The results of quality analysis and pedestrian level of service can be used as a basic reference for the government as a provider of pedestrian ways.